2022
DOI: 10.1097/im9.0000000000000102
|View full text |Cite
|
Sign up to set email alerts
|

Global transmission of HIV-1 subtype C and its impact on the circulation of B/C recombination strains in China

Abstract: This study aimed to reconstruct the origin and worldwide epidemic history of human immunodeficiency virus (HIV) 1 subtype C and comprehend how HIV-1 subtype C was introduced into and spread throughout China in the form of B/C recombinant strains. Envelope sequences of HIV-1 subtype C and some other subtypes deposited before December 31, 2020 were downloaded from the Los Alamos HIV Database and the Chinese National Center for AIDS/STD Control and Prevention Database. The available sequences were screened for qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Regarding the observed transmission dynamics between Africa and Asia, a recent study from China suggested that the seeding of subtype C from southern Africa into India occurred in 1977, which subsequently exported the virus to China via multiple introductions [42].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the observed transmission dynamics between Africa and Asia, a recent study from China suggested that the seeding of subtype C from southern Africa into India occurred in 1977, which subsequently exported the virus to China via multiple introductions [42].…”
Section: Discussionmentioning
confidence: 99%
“…According to a nationwide molecular epidemiological research study in 2012, there were over 11 HIV-1 subtypes and circulating recombinant forms (CRFs) in China, among which CRF07_BC (35.5%), CRF01_AE (27.6%), CRF08_BC (20.1%) and subtype B′ (9.6%) were the four dominant strains 13 . Liu et al 14 revealed that CRF07_BC and CRF08_BC emerged in 1988 and 1990, following the previous introduction of the HIV-1 B strain from Southeast Asia and the C strain from north India. The CRF01_AE was first introduced into China in seven clusters in cross heterosexual groups visiting southeast Asian countries 15 and later became the most prevalent strains for sexual transmission (44.54%) in China, 16 especially among men-who-have-sex-with-men (57.36%) 17 …”
mentioning
confidence: 99%